Tax Burden and Migration : A Political Economy Perspective - Sadka, Efraim (IMF Working Papers; Working Paper ;, 1997)
The extent of taxation and redistribution policy is generally determined at a political-economy equilibrium by a balance between those who gain and those who lose from a more extensive tax-transfer policy. In a stylized model of migration and human capital formation, we find, somewhat against conventional wisdom, that low-skill migration may lead to a lower tax burden and less redistribution than no migration, even though the migrants join the pro-tax coalition.